2023
DOI: 10.22454/fammed.2023.694219
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Contraceptive Implant Training in New Jersey Family Medicine Residencies: A Qualitative Study

Abstract: Background and Objectives: The aim of this study was to examine experiences of New Jersey family medicine residents and preceptors with the etonogestrel subdermal contraceptive implant and to explore barriers to and facilitators of training. Methods: In this qualitative study, we conducted semistructured individual interviews to explore residents’ and preceptors’ experiences with contraceptive implant procedural training. We invited residents and preceptors from programs with high (5.2–10.9) and low (0.0–0.1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Since then, several studies have demonstrated that this route of administration provides a safety profile and effective therapy without the fluctuations in blood levels commonly seen with transdermal administration [ 10 , 11 , 12 , 13 , 14 ]. The administration of hormone implants has been used worldwide for decades and it has increased after the etonogestrel implant (Nexplanon) was disseminated worldwide as an effective and safe contraceptive method [ 15 ]. In some countries, such as Brazil, non-absorbable implants (Silastic) are widely used to treat menopause, contraception, and endometrioses ( Figure 2 ) [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have demonstrated that this route of administration provides a safety profile and effective therapy without the fluctuations in blood levels commonly seen with transdermal administration [ 10 , 11 , 12 , 13 , 14 ]. The administration of hormone implants has been used worldwide for decades and it has increased after the etonogestrel implant (Nexplanon) was disseminated worldwide as an effective and safe contraceptive method [ 15 ]. In some countries, such as Brazil, non-absorbable implants (Silastic) are widely used to treat menopause, contraception, and endometrioses ( Figure 2 ) [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%